2005
DOI: 10.1097/01.sla.0000171035.57236.d7
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative ERCP Versus Laparoscopic Choledochotomy for Clearance of Selected Bile Duct Calculi

Abstract: These data suggest that the majority of secondary BD stones can be diagnosed at the time of cholecystectomy and cleared trans-cystically, with those failing having either choledochotomy or postoperative ERCP. However, because of the small trial size, a significant chance exists that small differences in outcome may exist. We would avoid choledochotomy in ducts less than 7 mm measured at the time of operative cholangiogram and severely inflamed friable tissues leading to a difficult dissection. We would advocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
1
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(147 citation statements)
references
References 24 publications
5
131
1
9
Order By: Relevance
“…These factors are those clearly related to the incidence and mechanism of post-ERCP pancreatitis in different analyses [31][32][33][34] . It is also remarkable that after laparoscopic CBD exploration, acute pancreatitis can be comparably high to sequential ERCP-ES (7.3% vs 8.8%) [12] . Certainly standard ERCP whenever possible should be limited because, as suggested by experienced endoscopists the only sure way to avoid post-ERCP complications is to avoid ERCP itself [35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors are those clearly related to the incidence and mechanism of post-ERCP pancreatitis in different analyses [31][32][33][34] . It is also remarkable that after laparoscopic CBD exploration, acute pancreatitis can be comparably high to sequential ERCP-ES (7.3% vs 8.8%) [12] . Certainly standard ERCP whenever possible should be limited because, as suggested by experienced endoscopists the only sure way to avoid post-ERCP complications is to avoid ERCP itself [35] .…”
Section: Discussionmentioning
confidence: 99%
“…F i r s t, t h e t r e a t m e n t o f C B D s t ones in cholecystectomized patients today remains the exclusive work of the endoscopist who often performs a salvage procedure for the patient and helps the surgeon as well [9][10][11] . This endoscopic approach is highly effective [12] with sporadic mortality and minimal early and late morbidity, all anyway lower when compared to surgical interventions. The surgical approach is therefore never proposed today as a first option in cholecystectomized patients and moreover the endoscopic treatment with ERCP-ES is never considered wrong or dangerous for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nathanson et al [16] conducted a study wherein they compared single stage laparoscopic management with delayed endoscopic management of intraoperatively discovered CBD stones. Patients were included only if the transcystic approach failed to clear the intraoperatively discovered CBD stones.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Several cohort studies have shown that two thirds of the stones detected by intraoperative cholangiography can be removed via the transcystic approach [16]. For patients in whom transcystic extraction of CBD stones fails, laparoscopic choledochotomy and stone extraction may be performed.…”
Section: Stones Discovered Intraoperativelymentioning
confidence: 99%
“…Also, when patients proceed to EM, a significant number of them may not have stones. 22,23 The incidence of bile duct stones has previously been shown to rise markedly in the presence of acute cholangitis, the operative mortality rate without cholangitis being 1.2% compared with 11.9% in patients with cholangitis. 24 The absence of mortality in the present series may well be related to the successful treatment of preoperative sepsis.…”
Section: 10mentioning
confidence: 99%